Employing the KEDA Model in Evaluating the Performance of Industrial Companies in Palestine and Jordan during the Years 2021 and 2022 - Salem, Salem Mohammad; Zbayneh, Saeid Abdelkader (Journal of Economic, Administrative and Legal Sciences, 2025)
This study aimed to identify the KIDA model's ability to evaluate the financial performance (EPS) of industrial companies listed on the Palestine and Amman Stock Exchanges, by applying the KIDA model to 43 industrial companies listed on the Palestine and Amman Stock Exchanges during the period from 2021-2022. The current study uses Panel data from secondary sources of the financial statements of the listed industrial companies, and the empirical data was analyzed using the statistical program (R). This study finds the existence of a relationship between some of the financial ratios used in the KIDA model and performance evaluated by EPS as follows: The study indicated that there is a statistical relationship between the ROA (X1) and the cash-to-total assets ratio (X5) with the financial performance EPS. However, this study noted that there is no statistical significance between the financial ratios used in the KIDA model and EPS. The current study finds no relationship between the total equity to total debt ratio (X2) and EPS. Moreover, the study finds no relationship between the accounts and notes payable to total assets ratio (X3) and EPS. Also, this study finds no relationship between total sales to total assets ratio (X4) and EPS. These results may be attributed to the failure to activate KIDA model in industrial companies listed in both the Palestine and Amman Stock Exchanges. Finally, this study recommends activating the KIDA model in industrial companies due to its success in revealing the financial performance of these companies.
Keywords: Financial performance; Kida model; Palestine Stock Exchange; Amman Stock Exchange; EPS